1628a Future occupational health nursing roles. (24th April 2018) - Drummond, A
Abstract : Introduction: The role of Occupational Health Nurses (OHNs) depends on many factors, including legislation, population, geography, history, culture, industrial profile of hazards and risks, and on how occupational health (and safety) relates to the national health system. In most countries, occupational health services emerged towards the end of the 19th Century following the Industrial Revolution, and the stage of development of occupational services varies, with corresponding variation in the OHN role. Notwithstanding this, the role is well defined in the context of other members of the multidisciplinary team. Major changes to the world of work at the end of the 20th Century, including changing demographics, new ways of working and the rise of chronic diseases including mental health issues, are impacting occupational health in the 21 st Century, and, with an increasing pace of change, has implications for the future role of occupational health nursing. Methods: A review of relevant literature. Results: The functions of the OHN can be tracked over time, require a wide range of skills and encompass numerous roles. Interdisciplinary and inter-professional collaboration is important. Changes are emerging in many countries that re-orientate the focus to the health of the working age population, and is not confined to those exposed to work-related risk or even to those at work. While there is a public health dimension, occupational health professionals see themselves as well placed, trained, and experienced to play a key role in this development. Conclusion: This paper will speculate on the implications, for the role of the OHN, of the evolving model of occupational health; from health, environment and safety management, through sickness absence management and vocational rehabilitation, and more recently to the healthy workplace, which extends to a wider workplace health focus, including wellbeing and health risk management in and beyond the work setting.